Peripheral Artery Disease: Atherosclerosis, Decreased Nitric Oxide, and Vascular Arterial Stiffening - Melvin R. Hayden (Journal of Vascular Diseases)
Peripheral artery disease (PAD) is a chronic progressive accumulation of atherosclerotic lesions with varying degrees of arterial obstruction determining ischemic symptoms of the involved extremities. PAD is associated with decreased bioavailable nitric oxide due to endothelial cell dysfunction and the development and progression of vascular arterial stiffening (VAS). Atherosclerosis also plays an essential role in the development and progression of vascular arterial stiffening (VAS), which is associated with endothelial cell activation and dysfunction that results in a proinflammatory endothelium with a decreased ability to produce bioavailable nitric oxide (NO). NO is one of three gasotransmitters, along with carbon monoxide and hydrogen sulfide, that promotes vasodilation. NO plays a crucial role in the regulation of PAD, and a deficiency in its bioavailability is strongly linked to the development of atherosclerosis, VAS, and PAD. A decreased arterial patency may also occur due to a reduction in the elasticity or diameter of the vessel wall due to the progressive nature of VAS and atherosclerosis in PAD. Progressive atherosclerosis and VAS promote narrowing over time, which leads to impairment of vasorelaxation and extremity blood flow. This narrative review examines how atherosclerosis, aging and hypertension, metabolic syndrome and type 2 diabetes, tobacco smoking, and endothelial cell activation and dysfunction with decreased NO and VAS with its increased damaging pulsatile pulse pressure result in microvessel remodeling. Further, the role of ischemia and ischemia–reperfusion injury is discussed and how it contributes to ischemic skeletal muscle remodeling, ischemic neuropathy, and pain perception in PAD.